1999
DOI: 10.1046/j.1365-2680.1999.00115.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo demonstration of α‐adrenoceptor‐mediated positive inotropy in pithed rats: evidence that noradrenaline does not stimulate myocardial α‐adrenoceptors

Abstract: 1. This study examines whether positive inotropy via alpha-adrenoceptors could be observed in vivo in pithed rats. Cardiac contractility was measured as the maximum rate of rise of left ventricular pressure (dP/dt(max)). Heart rate and aortic blood pressure were also recorded. 2. The selective alpha1-adrenoceptor agonists, methoxamine, cirazoline, amidephrine and phenylephrine caused dose-related increases in dP/dt(max). This response was progressively reduced by increasing doses of the alpha1-adrenoceptor ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In this study, as previously with exendin‐4, the enhanced pressor effect of GLP‐1(7–36) seen with propranolol treatment did not occur when the animals were treated with phentolamine together with propranolol. Because this could not be explained by a marked diminution by phentolamine of the vasoconstrictor effects, we suggest it is due to inhibition of a cardiac α‐adrenoceptor‐mediated positive inotropic effect (Broadley et al ., 1999). It was interesting that there was no evidence for a major contribution from α‐adrenoceptors to the vasoconstrictor effects of GLP‐1(7–36).…”
Section: Discussionmentioning
confidence: 93%
“…In this study, as previously with exendin‐4, the enhanced pressor effect of GLP‐1(7–36) seen with propranolol treatment did not occur when the animals were treated with phentolamine together with propranolol. Because this could not be explained by a marked diminution by phentolamine of the vasoconstrictor effects, we suggest it is due to inhibition of a cardiac α‐adrenoceptor‐mediated positive inotropic effect (Broadley et al ., 1999). It was interesting that there was no evidence for a major contribution from α‐adrenoceptors to the vasoconstrictor effects of GLP‐1(7–36).…”
Section: Discussionmentioning
confidence: 93%
“…A negative inotropic effect of ␣ 1 -adrenoceptor stimulation in the mouse myocardium has been reported (37). On the other hand, positive inotropic responses have been observed in rats both in vivo (6) and in vitro (14) upon ␣ 1 -adrenoceptor stimulation. In the present study, we showed that ␣ 1 -adrenoceptor stimulation with PE increased contractility and accelerated relaxation, which were accompanied, respectively, with an increased amplitude of Ca 2ϩ release from the SR and faster removal of Ca 2ϩ from the cytosol.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that ␤ 1 -adrenoceptor activation increases contraction and accelerates relaxation (10, 64). There is also evidence showing that ␣ 1 -adrenoceptor activation triggers positive inotropic responses in the rat myocardium (6,14). We recently demonstrated that testosterone enhances injury responses and contractile recovery to stimulation of both ␣ 1 -and ␤ 1 -adrenoceptors as well as enhances the expression of both adrenoceptor subtypes (56).…”
mentioning
confidence: 99%
“…However, we do not believe this additional effect of phentolamine on the pressor response was due only to suppression of the hindquarters vasoconstrictor action of exendin-4 because there was no hindquarters vasoconstrictor response to exendin-4 in the presence of ICI 118551, when the pressor effect of exendin-4 was augmented to a similar extent. Hence, the most likely explanation of the ability of phentolamine to suppress the increase in the pressor effect of exendin-4 caused by propranolol is that this was due to inhibition of another mechanism, e.g., a cardiac ␣ adrenoceptor-mediated positive inotropic effect, most likely attributable to adrenaline (Broadley et al, 1999). So, our results are consistent with the sympathoadrenal activation caused by exendin-4 resulting in substantial adrenaline release causing activation of cardiac ␣ and ␤ adrenoceptors and (largely) hindquarters ␤ 2 adrenoceptors, with little evidence of activation of vascular ␣ adrenoceptors, either through this mechanism or through mediation of sympathetic efferent noradrenergic vasoconstrictor activity.…”
Section: Discussionmentioning
confidence: 99%